Effects of electronic excitation on cascade dynamics in tungsten - Sheng, Shaoding; Wei, Shuwan; Zhang, Chengling; Zhang, Chao; Pu, Guo; Li, Bing-Sheng (Frontiers in Physics, 2025)
While tungsten has emerged as a primary candidate for plasma-facing components in future fusion devices, the effects of electronic excitations on the irradiation damage behavior under high-energy irradiation remain unclear. In this work, using a two-temperature (2T-MD) model in molecular dynamics simulations, we investigated the effects of irradiation energy, irradiation temperature, electron density and the electron-phonon (e-ph) coupling activation time on the cascade dynamics in tungsten. The results showed that the electronic effect has significant impacts on the formation of irradiation defects, especially under high-energy irradiation. Compared with the results of classical molecular dynamics calculations, the numbers of peak and surviving defects calculated using 2T-MD model were significantly reduced under high-energy ion irradiation (∼150 keV). The number of peak defects increased with temperature, while the surviving defects showed a similar number. With the increase of electron density, the number of peak defects decreased. However, the number of surviving defects was almost unaffected by the electron density. The later the e-ph coupling activation time, the more the number of peak and surviving defects. The mechanisms were well explained by analyzing the local atomic and electronic temperatures. Our work provides valuable information for understanding the electronic effects on the primary radiation damage in tungsten.